ANALISIS PENGARUH GAYA HIDUP, KELOMPOK REFERENSI DAN LOKASI TERHADAP KEPUTUSAN BERKUNJUNG DI WARUNG KOPI AMING KOTA PONTIANAK - admin, Yella Febrinda B11112074 (Jurnal Manajemen Update, 2017)
This study aimed to analyze and determine the influence of lifestyle, reference groups, and the location of the decision been in the Coffee Shop Aming Pontianak. This type of research used in this study is a survey research, with analysis of quantitative data. In pennelitian survey, collecting data using questionnaires. The analysis technique used in this research is multiple regression analysis using SPSS version 22.0. The findings show that lifestyle variables, reference groups and locations together significant and positive impact on the decision variables visit. By 24.8% visited a decision variable can be explained by the independent variable while the remaining 75.2% is explained by other variables outside of this study. Keywords: lifestyle, reference groups, the location, the decision to visit